The Effect of Product Innovation and Entrepreneurial Marketing on SME Competitive Advantage - Damanik, Michael Joy Rade; Aisyah, Nur (Golden Ratio of Data in Summary, 2024)
This study aims to determine the effect of product innovation and entrepreneurial marketing on the competitive advantage of SME in Medan Tuntungan District, North Sumatra. This type of research uses quantitative methods. The population of this study were all SME in Medan Tuntungan District, totaling 375 SME, and the number of samples obtained from calculations using the Slovin formula, namely 79 samples. The results obtained from this study are that partially product innovation has a positive and significant effect on competitive advantage with a t-calculated of 2.895 and a t-estimated worth 1.99 so that the t-calculated> t-estimated (2.895> 1.99) and the significance value is smaller than 0.05 (0.025 <0.05). Likewise, the entrepreneurial marketing variable has a positive and significant effect on competitive advantage with a t-calculated of 2.014 and a t-estimated worth 1, 99 so that the t-calculated> t-estimated (2.014> 1, 99) and a significance value smaller than 0.05 (0.019 < 0.05). While simultaneously, product innovation (X1) and entrepreneurial marketing (X2) together have a positive and significant effect on the competitive advantage of SME in Medan Tuntungan District with an F-calculated value of 4.027 and an F-estimated value of 3.12, so 4.027> 3.12 with a significance value of 0.022 < 0.05.